2013
DOI: 10.1890/12-0215.1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an age‐dependent influence of environmental variations on a long‐lived seabird's life‐history traits

Abstract: Theoretical and empirical studies have highlighted the effects of age on several life-history traits in wild populations. There is also increasing evidence for environmental effects on their demographic traits. However, quantifying how individuals differentially respond to environmental variations according to their age remains a challenge in ecology. In a population of Black-browed Albatrosses monitored during 43 years, we analyzed how life-history traits varied according to age, and whether individuals of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
117
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(127 citation statements)
references
References 62 publications
10
117
0
Order By: Relevance
“…This suggests that senescence starts at this age and thus that the population can be divided into 3 age classes: juveniles, adults and senescing individuals, as in other long-lived seabird species (Pardo et al 2013). Senescing individuals have higher mortality compared to younger adults and could also be influenced by reproductive senescence as a consequence of altered foraging capacities of older individuals, in accordance with similar findings for black-browed albatross (Pardo et al 2013). We found similar λ in Scenarios A and B (respectively accounting or not for senescence); this may be explained by the fact that there were very few females alive after Year 16.…”
Section: Storm Petrel Mortality and Senescencementioning
confidence: 98%
See 1 more Smart Citation
“…This suggests that senescence starts at this age and thus that the population can be divided into 3 age classes: juveniles, adults and senescing individuals, as in other long-lived seabird species (Pardo et al 2013). Senescing individuals have higher mortality compared to younger adults and could also be influenced by reproductive senescence as a consequence of altered foraging capacities of older individuals, in accordance with similar findings for black-browed albatross (Pardo et al 2013). We found similar λ in Scenarios A and B (respectively accounting or not for senescence); this may be explained by the fact that there were very few females alive after Year 16.…”
Section: Storm Petrel Mortality and Senescencementioning
confidence: 98%
“…Some demographic traits of the storm petrel were described in previous studies (Sanz-Aguilar et al 2008, Soldatini et al 2014, but information on senescence and age effects on the species' demography is still lacking. In particular, the differential re sponses of age classes to environmental constraints shape survival and reproductive traits at a population level and probably in fluence the response of populations to global climate change (Pardo et al 2013). As a consequence, in order to understand the influence of future climate on this and other seabird species, an assessment on how climate is currently related to population metrics is needed (McClure et al 2013).…”
Section: Research Approach and Hypothesesmentioning
confidence: 99%
“…[16,19,20]). In the wild, studies of FS have largely focused on long-lived, large-bodied animals that face relatively low levels of environmental hazard (ungulates [10,21], sea-birds [22], seals [23] and primates [6,24]). Because FS is more detectable when EM is low, this taxonomic bias may lead to an overestimation of the prevalence of FS compared with the influences of selective disappearance in natural populations across species.…”
Section: Introductionmentioning
confidence: 99%
“…Age-specific differences in breeding performance have been observed in several seabirds (Nevoux et al, 2007;Vieyra et al, 2009;Pardo et al, 2013). In most cases young individuals perform less well than older individuals (Martin, 1995), thereby indicating improvement in performance with age leading to a peak and then decline (i.e., senescence) (Clutton-Brock, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, few studies have ever examined at the same time how environmental conditions affect age patterns in breeding performance (Bunce et al, 2005;Pardo et al, 2013;Oro et al, 2014). Depending on environmental conditions, different age patterns can exist (see Oro et al, 2014): in most studies, either (a) differences among age classes in breeding performance were found to decrease under better environmental conditions (Sydeman et al, 1991;Laaksonen et al, 2002;Barbraud and Weimerskirch, 2005;Bunce et al, 2005) or (b) environmental conditions had no clear influence on breeding performance (Nevoux et al, 2007;Vieyra et al, 2009;Lee, 2011;Pardo et al, 2013); just one study found that differences between age-classes were greater under favorable environmental conditions (Oro et al, 2014).…”
Section: Introductionmentioning
confidence: 99%